Hybrid localization algorithm based on received signal strength and angle-of-arrival for indoor location estimation - Mahmood F. Mosleh; Riam M. Zaal; Eyad I. Abbas (Universitas Ahmad Dahlan, 2021)
The huge ubiquitous deployment of wireless technologies and the pervasive availability of smart devices, indoor localization has become one of the most interesting topics in numerous location-based services. Where several methods have been adopted to estimate and localize the mobile and user location. The earliest and most interesting method was based on received signal strength (RSS) measurement. However, such method has showed weakness in handling the accurate estimation results. Recently, researchers start gather several different methods to achieve the advantages of each method and achieve higher accurate estimation. Hence, in this paper a hybrid localization algorithm has been designed and proposed based on the use of both RSS and angle-of-arrival (AoA). The algorithm has been tested in a three-dimensional indoor building; we are taking the effects of different building materials. The results were obtained depending on the measurement of RSS and AoA gathered from each received point and by using two AP devices for more accuracy in positioning coordination, the type of the transmitters is directional.